Analysis of the Effectiveness of Modified Chicken Foot (CAM) in Reducing Pavement Settlement on Embankments on the Trans-Sumatra Toll Road - Bagas Dwi Purwantoro; Trihanyndio Rendy Satrya; Ria Asih Aryani Soemitro (International Journal Labs, 2025)
The construction of the Trans Sumatra Toll Road (JTTS) Betung – Jambi Section 1B faces challenges due to highly compressible soft soil conditions, which have the potential to cause excessive settlement and embankment stability problems. This study aims to optimize embankment management at STA 43+225 – 43+375 which was initially a 2m replacement by evaluating the effectiveness of Modified Chicken Foot (CAM), combined with variations in replacement depth from 0 to 2 m. The analysis was carried out using the finite element method with the PLAXIS 2D assisted program to compare the performance of consolidation settlement and safety factor ( SF ). The results showed that the application of CAM provided a delay effect ( delaytime ) on the initial settlement rate and significantly reduced the total settlement. The combination of Replacement 2 m + CAM showed optimal performance, suppressing the settlement of 5 m embankment to 0.811 m (reduced by 17% from the alternative without CAM. In addition, the application of CAM was proven to improve stability, with the highest SF value reaching 2,055 on a 3 m embankment without replacement.